Objectifying acupuncture effects by lung function and numeric rating scale in patients undergoing heart surgery - Maimer, Anna; Remppis, Bjoern-Andrew; Sack, Falk-Udo; Ringes-Lichtenberg, Stefanie; Greten, Tobias; Brazkiewicz, Frank; Schröder, Sven; Goncalves, Mario; Efferth, Thomas; Greten, Henry Johannes (Evidence-based complementary and alternative medicine, 2013)
Rationale. Poststernotomy pain and impaired breathing are common clinical problems in early postoperative care following heart surgery. Insufficiently treated pain increases the risk of pulmonary complications. High-dose opioids are used for pain management, but they may cause side effects such as respiratory depression. Study Design. We performed a prospective, randomized, controlled, observer-blinded, three-armed clinical trial with 100 patients. Group 1 ( ) and Group 2 ( ) received one 20 min session of standardized acupuncture treatment with two different sets of acupoints. Group 3 ( ) served as standard analgesia control without additional intervention. Results. Primary endpoint analysis revealed a statistically significant analgesic effect for both acupuncture treatments. Group 1 showed a mean percentile pain reduction (PPR) of 18% (SD 19, ). Group 2 yielded a mean PPR of 71% (SD 13, ). In Group 1, acupuncture resulted in a mean forced vital capacity (FVC) increase of 30 cm3 (SD 73) without statistical significance ( ). In Group 2, posttreatment FVC showed a significant increase of 306 cm3 (SD 215, ). Conclusion. Acupuncture revealed specific analgesic effects after sternotomy. Objective measurement of poststernotomy pain via lung function test was possible.
Gesehen am 16.06.2021